In vitro Propagation of Thuja occidentalis Through Apical Shoot Culture - Kabir, MH; Roy, PK; Ahmed, Golam (Plant Tissue Culture and Biotechnology, 2008)
In vitro plant regeneration of Thuja occidentalis was obtained in apical shoot cultures from field grown plants. Hormone free MS medium 100% explants produced shoots. The average number of shoots per explant was 6.57 ± 0.45 and the average shoot length of 4.5 ± 0.27 cm were recorded in this medium. Shoots rooted well when they were transferred into half strength MS with 1.0 mg/l IBA. The average number of root per shoot was 3.92 ± 0.28 and the average root length of 3.64 ± 0.38 cm were observed in this medium. No morphological variants were observed during the passage of in vitro culture. Key words: In vitro, Propagation, Thuja occidentalis, Apical shoot DOI = 10.3329/ptcb.v16i1.1099 Plant Tissue Cult. & Biotech. 16(1): 5-9, 2006 (June)